Right-Wing Leftists, Left-Wing Rightists, and Traditionalist Liberals: Core Political Values and Ideological Inconsistency at the Party-Elite Level in Bulgaria - Martin Konstantinov (Social Sciences, 2023)
The growth of heterodox ideological configurations, or ideological inconsistencies, among the electorate of Western countries, has been offered as one explanation for recent momentous political events, such as Brexit or the election of Donald Trump as US President. Previous research, however, suggests that ideological inconsistency has been typical for Central and Eastern European (CEE) states for the past thirty years after the fall of the Socialist regimes there. Based on a survey of 102 active members of local and national party structures in Bulgaria, followed by in-depth interviews with the same respondents, I develop a conceptual and methodological approach aimed at objectively measuring Bulgarians’ political values and ideological orientations. Building on previous research on the statistical independence of the social and economic dimensions of ideology, this study identifies three main models of ideological inconsistency at the party-elite level in Bulgaria, offering evidence of the “homogeneity in ideological inconsistency” in this post-Socialist country, with party elites and electorate following the same patterns of inconsistency. The existence of a conservative value complex, integrating traditionalist, statist, and nationalist attitudes regarding the social sphere, is another major finding of the study. I discuss the specific historical and socio-cultural background contributing to ideological inconsistency in Bulgaria and potential implications for the wider CEE region.